THE POLITICAL ECONOMY OF ENVIRONMENTAL POLICY WITH OVERLAPPING GENERATIONS. (August 2014) - Karp, Larry; Rezai, Armon
<x xml:space="preserve">Abstract</x> A two‐sector overlapping generations model illuminates the intergenerational effects of a tax that protects an environmental stock. A traded asset capitalizes the economic returns to future tax‐induced environmental improvements, benefiting the current asset owners, the old generation. Absent a transfer, the tax harms the young generation by decreasing their real wage. Future generations benefit from the tax‐induced improvement in environmental stock. The principal intergenerational conflict arising from the tax is between generations alive at the time society imposes the policy, not between generations alive at different times. A Pareto‐improving tax can be implemented under various political economy settings.